Characterization and antimicrobial activity of a novel lytic phage vB_SmaS_QH16 against Stenotrophomonas maltophilia: in vitro, in vivo, and biofilm studies - Cheng, Peng; Li, Zian; Liu, Lanmin; Li, Ruizhe; Zhou, Jianwu; Luo, Xiaoqin; Mu, Xiaoming; Sun, Jingwei; Ma, Jideng; A, Xiangren (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundStenotrophomonas maltophilia, an important opportunistic pathogen resistant to multiple antibiotics, necessitates alternative therapies. Phages, with their high specificity and bacteriolytic ability, are emerging as promising antibiotic alternatives. This study aimed to isolate and characterize a novel lytic phage targeting S. maltophilia and to evaluate its antibacterial potential.MethodsA novel lytic phage, vB_SmaS_QH16, was isolated from hospital sewage using S. maltophilia no.981 as the host. Phage morphology was analyzed using transmission electron microscopy (TEM), and genome sequencing and annotation were performed. Host range, efficiency of lysis (EOP), optimal multiplicity of infection (MOI), one-step growth curves, and physicochemical stability were also determined. Biofilm inhibition and eradication were assessed using crystal violet staining, MTT assays, and acridine orange fluorescence microscopy. Using Galleria mellonella and mouse infection models, the in vivo anti-infective effects of phages were evaluated.ResultsPhage vB_SmaS_QH16, a member of the class Caudoviricetes, has a 43,500 bp genome with 64 open reading frames (ORFs) and no virulence, antibiotic resistance, or lysogeny-related genes. It exhibits a broad host range, lysing 47.95% (35/73) of tested S. maltophilia strains. The optimal MOI was 0.01, with an average burst size of 37.69 PFU/cell. The phage is stable at 4–50 °C and pH 3.0–11.0 but is highly sensitive to UV light. It effectively inhibits biofilm formation and eradicates mature biofilms in a concentration-dependent manner. In vitro, the phage significantly suppresses bacterial growth, though resistant mutants emerge over time. In vivo, vB_SmaS_QH16 increases the survival rates of larvae and mice, with a higher MOI offering better protection.ConclusionsPhage vB_SmaS_QH16 shows therapeutic potential against S. maltophilia infections, characterized by a broad host range, efficient lytic capability, and biofilm-disrupting activity. Its stability and safety further support its clinical application potential. Future research should explore its biofilm disruption mechanisms and monitor resistance development. Additionally, since its efficacy has been validated in mammalian models, further studies can focus on advancing its clinical translation.